The triolein/aqueous interface and lipase activity studied by spectroscopic ellipsometry and coarse grained simulations. (March 2018) - Stamm, Arne; Svendsen, Allan; Skjold-Jørgensen, Jakob; Vissing, Thomas; Berts, Ida; Nylander, Tommy
Graphical abstract: Highlights: The results suggest that water can be taken up by a triolein oil phase. The uptake of water in the oil phase is affected by lipase adsorption/activity. The thickness increase of a triolein film exposed to water was enhanced by active lipase but reduced with an inactive enzyme mutant. Abstract: In spite of the importance of the triglyceride aqueous interface for processes like emulsification, surfactant interactions and lipase activity, relatively little is known about this interface compared to that between alkanes and water. Here, the contact between triolein and water was investigated in terms of water inclusion in the oil phase and orientation of the molecules at the interface. Coarse grained models of triglycerides in contact with water were constructed and correlated with experimental results of the changes in thickness and refractive index, obtained using spectroscopic ellipsometry of spin-coated triolein films. The topography of the layer was revealed by atomic force microscopy. Dry triolein and a triolein sample after equilibration with water were also compared structurally using small-angle X-ray scattering. Additionally, the kinetics of adsorption/activity of three different variants of the Thermomyces lanuginosus lipase (TLL) were investigated. The results show that uptake of water in the triolein phase leads to increase in thickness of the layer. The observed increase of thickness was further enhanced by an active lipase but reduced when an inactive mutant of the enzyme was applied.